Understanding social-ecological changes in Fairbairn village, Eastern Cape - Falayi, Menelisi (Rhodes University, Faculty of Science, Department of Environmental Science, 2017)
The world is becoming increasingly complex and uncertain due to increasing levels of social- ecological change. Rural communities in sub-Saharan Africa are faced with multiple interconnected challenges such as population growth, environmental change, economic recession and climatic changes, amongst others. Such challenges can play a key role in determining vulnerability and food security, particularly for natural resource product- dependent societies that have limited livelihood sources. Studies that consider understanding how society and ecosystems simultaneously interact and respond to new and exacerbated drivers are increasingly needed. Therefore, this study was conducted in Fairbairn village, Eastern Cape, South Africa with the purpose of exploring multi-scale historical processes and current related trends in livelihood and environmental change, and the implications for future trajectories under a changing climate. This study applied social-ecological thinking and several conceptual approaches were combined to provide a lens for exploring the changes taking place. These included, inter alia, complexity theory, social-ecological systems, the sustainable livelihoods approach and the Intergovernmental Platform on Biodiversity and Ecosystem Services framework and principles. The study employed a mixed method approach to gather data, which included a household survey, aerial photography, historical records as well as Participatory Learning and Action, focus group discussions, and Participatory Scenario techniques. Quantitative data were analysed using Excel and Statistica version 13, whilst coding was used for thematic analysis of qualitative data. The main objective of this study was to explore multi-scale historical processes and current related trends of livelihood and environmental change, and the implications of these for future trajectories under a changing climate. Livelihood and landscape changes in Fairbairn village are embedded within a history of direct state intervention and more recently, improvements in basic service delivery. The findings show that natural resource products still form an important part of people's livelihoods despite many other changes over the last fifteen years. A high proportion of households continue to utilise different products to meet household needs. The most widely used products are fuelwood, wild herbs and wild fruits. More so, my results revealed a significant increase in the number of people commercialising natural resource products over the past fifteen years. Furthermore, I found that rural livelihoods in Fairbairn are heavily dependent on external income and consumption and have become increasingly divorced from local production patterns. My results depict a steady decline of cultivated fields with a corresponding increase of home gardens since the 1960s. Therefore, the results demonstrate that current livelihood strategies are an expression of historical processes interacting with current contextual complexities. Given the complex and multidimensional issues at play in Fairbairn, the study highlights that there is no straightforward answer regarding future livelihood strategies. However, participatory scenario deliberations revealed that the youth were much more open to diversified and even very different forms of livelihood strategies in the future, whilst community leaders and elders remained firmly attached to farming activities. Understanding the diversity of past livelihood changes, together with current trends, can help to better contextualise future livelihood trajectories and this can therefore help rural communities identify and avoid undesirable futures under a changing climate.
Keywords: Fairbairn Village (Eastern Cape, -- South Africa); Rural development -- South Africa -- Eastern Cape -- Fairbairn Village; Land tenure -- South Africa -- Eastern Cape -- Fairbairn Village